Absence of tmRNA Increases the Persistence to Cefotaxime and the Intercellular Accumulation of Metabolite GlcNAc in Aeromonas veronii - Yu, Wenjing; Li, Daiyu; Li, Hong; Tang, Yanqiong; Tang, Hongqian; Ma, Xiang; Liu, Zhu (Frontiers in Cellular and Infection Microbiology, 2020)
Bacterial persisters are a small proportion of phenotypically heterogeneous variants with transient capability to survive in high concentrations of antibiotics, causing recurrent infections both in human and aquatic animals. Transfer-messenger RNA (tmRNA), which was encoded by ssrA gene, was identified as a determinant regulator mediating the persistence to β-lactams in pathogenic Aeromonas veronii C4. The deletion of tmRNA exhibited the increased ability of persister formation primarily due to the inhibition of protein synthesis. Transcriptomic and metabolomic analyses revealed that, absence of tmRNA not only significantly elevated the intercellular levels of metabolite GlcNAc and promoted NaCl osmotic tolerance, but also up-regulated the expression of metabolic genes in both the upsteam biosynthesis pathway and the downstream metabolic flux of peptidoglycan (PG) biosynthesis. Finally, exogenous GlcNAc stimulated significant bacterial growth, enhanced content of GlcNAc in cell wall, higher resistance to osmotic response, and higher persistence to cefotaxime in a concentration dependent manner, implying its potential role in promoting the multiple phenotypes observed in tmRNA deletion. Taken together, these results uncovered a novel mechanism of persister formation mediated by tmRNA against the β-lactam challenges.